The Trinity Six - Cumming, Charles, 1971- (St. Martin's Press, 2011)
Hard-up Russia expert Dr. Sam Gaddis finally has a lead for a book that could set his career back on track. He has staggering new information about an unknown sixth member of the infamous Cambridge spy ring -- a man who has evaded detection for his entire life. But when his source suddenly dies, Gaddis is left with just shreds of his investigation, and no idea that he is already in too deep.